2013
DOI: 10.1016/j.neurobiolaging.2012.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Age effect on the default mode network, inner thoughts, and cognitive abilities

Abstract: Age-related effects on the Default Mode Network (DMN) connectivity as measured at rest using functional MRI (fMRI) are now well described. Little is known however about the relationships between these changes and age-related effects on cognition or on the unconstrained thoughts occurring during the resting-state scan, called as inner experience.Brain resting-state activity, inner experience and cognitive ability measurements were obtained in 70 participants aged 19 to 80 years. The anterior-posterior disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
83
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 40 publications
15
83
0
1
Order By: Relevance
“…Reduced connectivity of mPFC node from temporal and posterior parts of DMN in aged subjects was evident even with a relatively low number of subjects (in sample 2 ). Group comparisons suggested that the most significant effect of age was present in the coupling between mPFC and posterior midline structures, in agreement with other studies (Andrews-Hanna et al, 2007; Tomasi and Volkow, 2012; Campbell et al, 2013; Mevel et al, 2013). These areas form the nucleus of DMN which is composed by other several subsystems (Laird et al, 2009) involving temporal, superior frontal and lateral parietal cortices.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Reduced connectivity of mPFC node from temporal and posterior parts of DMN in aged subjects was evident even with a relatively low number of subjects (in sample 2 ). Group comparisons suggested that the most significant effect of age was present in the coupling between mPFC and posterior midline structures, in agreement with other studies (Andrews-Hanna et al, 2007; Tomasi and Volkow, 2012; Campbell et al, 2013; Mevel et al, 2013). These areas form the nucleus of DMN which is composed by other several subsystems (Laird et al, 2009) involving temporal, superior frontal and lateral parietal cortices.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, age-related reductions in DMN nodes seems to involve coupling between mPFC and posterior midline structures in particular, which are the key nodes of the DMN (Andrews-Hanna et al, 2007; Bluhm et al, 2008; Biswal et al, 2010; Campbell et al, 2013; Mevel et al, 2013). Default Mode Network rs-fMRI connectivity predicts cognitive and behavioral measures, especially memory function, both in different populations including healthy young subjects (Sala-Llonch et al, 2012) and healthy elders (Andrews-Hanna et al, 2007; Damoiseaux et al, 2008; Wang et al, 2010; He et al, 2012; Mevel et al, 2013; Razlighi et al, 2014). Alterations in the DMN, a core brain network, have been attributed to inefficient reallocation of resources, though the exact causes of decreased DMN are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with previous work on the relation between cognitive capacity and the negative BOLD response in DMN, for example studies on normal aging [43,44], we suggest that insufficient suppression of DMN is related to the language impairment that was observed in GE participants in the present study.…”
Section: Inadequate Negative Bold Responsesupporting
confidence: 93%
“…However, it is not only the presence of correlated, task-positive brain networks that governs performance. Increasing evidence supports the hypothesis that anti-correlated networks are as important for human brain function as correlated networks [20,43,44].…”
Section: Inadequate Negative Bold Responsementioning
confidence: 87%
“…During normal aging (i.e., in the absence of neurodegenerative disease), individuals with marked reductions in DMN connectivity also show significant cognitive decline relative to age-matched subjects with stronger FC (7)(8)(9). This relationship appears particularly robust for associative memory (10)(11)(12), where the strength of temporal coherence between the hippocampus and posteriomedial areas of the DMN (i.e., the precuneus and cingulate cortex) predicts face-name memory performance (12). Although rs-dynamics are also disrupted in a number of other conditions (for a review, see ref.…”
mentioning
confidence: 99%